2012
DOI: 10.1103/physreve.86.030102
|View full text |Cite
|
Sign up to set email alerts
|

Criticality governed by the stable renormalization fixed point of the Ising model in the hierarchical small-world network

Abstract: We study the Ising model in a hierarchical small-world network by renormalization group analysis and find a phase transition between an ordered phase and a critical phase, which is driven by the coupling strength of the shortcut edges. Unlike ordinary phase transitions, which are related to unstable renormalization fixed points (FPs), the singularity in the ordered phase of the present model is governed by the FP that coincides with the stable FP of the ordered phase. The weak stability of the FP yields peculi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Our results give the two critical probabilities as p c1 = 0(< p BCZ c1 ) and p c2 = p BCZ c2 , implying that the system has only a critical phase and a percolating phase, and does not have a non-percolating phase for p > 0. As far as we know, all complex network models with a critical phase have only the critical phase and the percolating phase ( [8-11, 13-15, 19] for percolation and [12,19,[22][23][24][25][26][27] for spin systems). It will be challenging to clarify the origin of such universal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Our results give the two critical probabilities as p c1 = 0(< p BCZ c1 ) and p c2 = p BCZ c2 , implying that the system has only a critical phase and a percolating phase, and does not have a non-percolating phase for p > 0. As far as we know, all complex network models with a critical phase have only the critical phase and the percolating phase ( [8-11, 13-15, 19] for percolation and [12,19,[22][23][24][25][26][27] for spin systems). It will be challenging to clarify the origin of such universal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the iterative structure of hierarchical networks may facilitate their realization in engineered devices to unlock and control their unconven-tional behaviors. Work on percolation [15][16][17][18][19][20], the Ising model [21][22][23][24][25], and the q-state Potts model [26][27][28] have shown that critical behavior, once thought to be exotic and model-specific [4], can be categorized with the renormalization group [26] for a large class of hierarchical networks with a hyperbolic structure.…”
mentioning
confidence: 99%
“…[24] (see also Ref. [26]), we introduce the following couplings. All variables x i interact with their nearest-neighbors along the backbone with a coupling K 0 (solid links in Fig.…”
mentioning
confidence: 99%
“…These recursively defined structures provide deeper insights into small-world effects compared to random networks that otherwise require approximate or numerical methods. Work on percolation [6,17,[20][21][22], the Ising model [15,[23][24][25], and the q-state Potts model [19,26] have shown that critical behavior, once thought to be exotic and model-specific [3], can be universally categorized near the transition point [26,27] for a large class of hyperbolic networks, such as those discontinuous percolation transitions described in Refs. [6,14].…”
mentioning
confidence: 99%